An investigation into the cloud manufacturing based approach towards global high value manufacturing for smes - Hassanzadeh, Soheil; Cheng, Kai (Cranfield University Press, 2013)
Considering the high labour costs and intensive competitions in the global market, improving the effective deployment of innovative design and manufacturing and utilisation of all existing technical information, for the full life cycle of the product, is essential and much needed for manufacturing Small and Medium sized Enterprises (SMEs) in particular. Cloud Manufacturing , as a powerful tool supported with ‘big data’, will likely enable SMEs to move towards using dynamic scalability and ‘free’ available data resources in a virtual manner and to provide solution-based, value-added, digital-driven manufacturing service over the Internet. The research presented in this paper aims to develop a cloud manufacturing based approach towards value-added, knowledge/solution driven manufacturing for SMEs, where there are many constraints in engaging responsive high value manufacturing. The paper will present the framework, architecture and key moderator technologies for implementing cloud manufacturing and the associated application perspectives. The paper concludes with further discussion on the potential and application of the approach.
Keywords: Cloud manufacturing; Virtualised resources; Service-orientated manufacturing